2019
DOI: 10.24912/jmts.v2i4.6305
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Memengaruhi Penerapan Building Information Modeling (Bim) Dalam Tahapan Pra Konstruksi Gedung Bertingkat

Abstract: ABSTRAKSalah satu teknologi yang belakangan ini terus berkembang pada sektor industri Arsitektur, Teknik dan Konstruksi adalah Building Information Modeling atau disebut juga BIM. Teknologi BIM tersebut merupakan teknologi yang membantu proses pengerjaan konstruksi bangunan. Negara-negara di Asia Tenggara telah menggunakan teknologi BIM dalam praktik konstruksi, Namun di Indonesia penggunaan teknologi BIM ini masih belum banyak digunakan. Dengan adanya peraturan pemerintah no 2 tahun 2017 pasal 5 ayat 5 yang m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…From the analysis that has been carried out, the top five rankings for each variable of the benefits of BIM implementation for top-class and middle-class contractors are almost the same, not too different for the statement variables of the benefits of BIM implementation, the comparison shown in Table 4 and from the column chart visualization in Figure 2. In this study also make comparison based on from the top five rankings of benefits in BIM implementation from top-class contractors, middle-class contractors, and as well as from previous studies [8] shown in Table 5. The results of the data analysis carried out have found five dominant benefits in the implementation of BIM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the analysis that has been carried out, the top five rankings for each variable of the benefits of BIM implementation for top-class and middle-class contractors are almost the same, not too different for the statement variables of the benefits of BIM implementation, the comparison shown in Table 4 and from the column chart visualization in Figure 2. In this study also make comparison based on from the top five rankings of benefits in BIM implementation from top-class contractors, middle-class contractors, and as well as from previous studies [8] shown in Table 5. The results of the data analysis carried out have found five dominant benefits in the implementation of BIM.…”
Section: Resultsmentioning
confidence: 99%
“…Most likely studies focus on BIM application for the general construction industry (contractor, consultant, and others parties) [2]- [7]. The other study focused on BIM application for the contractor in general [8], the other focus on the regulation and dimension of BIM [9]. So, the previous studies haven't focused on BIM application in the sub-class contractors (top-class, middle-class, and low-class contractor) in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil ini menunjukkan bahwa tingkat penerapan BIM (Y) memiliki pengaruh yang positif dan signifikan terhadap kinerja mutu (Y2). (Nelson & Tamtana, 2019) menyatakan BIM mampu medeteksi konflik/kesalahan lebih awal dan mampu mencegahnya, BIM membantu dalam penarikan keputusan baik saat proses perencanaan dan desain, dan Implementasi BIM membangun sinergi antara pemangku kepentingan konstruksi (owner, kontraktor, konsultan, dsb). Semakin besar peningkatan BIM di proyek, maka kinerja mutu yang dihasilkan semakin meningkat pula.…”
Section: Pengaruh Tingkat Penerapan Bim (Y) Terhadap Kinerja Mutu (Y2)unclassified
“…Proyek konstruksi seringkali melibatkan sinkronisasi antara beberapa disiplin ilmu terkait, seperti: arsitektural, struktural, dan mekanikal elektrikal [6]. Terkadang apa yang seharusnya dikerjakan bersama oleh para engineer dilakukan secara terpisah karena tidak ada fasilitas terintegrasi [7].…”
Section: Autodesk Revitunclassified